Efektivitas Pendampingan Advokat terhadap Pelaku Penyalahgunaan Narkotika dalam Mewujudkan Keadilan Restoratif - Dananjaya, Made Adi Widhirestu; Gorda, AAA. Ngurah Tini Rusmini; Antari, Putu Eva Ditayani; Sukadana, Dewa Ayu Putri (Consensus : Jurnal Ilmu Hukum, 2025)
: The restorative justice paradigm views drug addicts as individuals who need physical, mental, and social recovery. This study analyses the role of advocates in restorative justice-based law enforcement. Using empirical legal methods, this study explores legal aid practices through interviews with advocates, law enforcement officials, addicts, and rehabilitation workers, as well as reviewing the Narcotics Law, Criminal Procedure Code, and Supreme Court Regulation No. 4 of 2014. The results show that advocates play an important role in ensuring that addicts are treated as victims, not criminals. Substantive assistance with medical and psychological evidence supports rehabilitation, while procedural assistance ensures due process of law. Non-litigious assistance such as counselling and family mediation also reinforces restorative principles. However, the effectiveness of legal aid is influenced by factors such as the competence of advocates, the alignment of the vision of officials, the availability of rehabilitation facilities, family support, and legal culture. The unpreparedness of these elements can hinder the implementation of restorative justice. Therefore, improving the quality of legal aid and synergy between institutions is very important to create a more humane criminal justice system for drug addicts.